Dispossession and legal mentalité in nineteenth-century South Africa: Grotian and Lockean theories of property acquisition in the annexations of British Kaffraria and Natalia. (2nd January 2021) - Reid, Darren
ABSTRACT: British and Afrikaner governments used different types of legal arguments to legitimize their acquisition of African land in the early nineteenth century. Using Pierre Legrand's concept of legal mentalité, I explore the legal mythologies that conditioned Britons' and Afrikaners' methods of land acquisition. I adopt two instances of land acquisition to use as case studies: the British annexation of Kaffraria in 1835 and the Afrikaner annexation of Natalia in 1839. I show that the annexation of British Kaffraria was conditioned by a legal mythology influenced by Lockean ideas of property theory, in which property could be legally obtained through a framework of improvement. Meanwhile, I show that the annexation of the Republic of Natalia was conditioned by a legal mythology influenced by Grotian ideas of property theory, in which property could be legally obtained through a framework of conquest.